Bertha's Secret Battle - Coldwell, John; Adapted by Calcutt, David; Illustrated by Weir, Doffy (New York Oxford University Press, 1998)
Treetops Playscripts are adaptations of popular stories from the Treetops series. All scripts are designed for classroom reading as well as staged performance, and can be performed by groups of as few as six actors. Ideal for use within the Literacy Hour.
Include Color Illustrations
Keywords: Readers (Elementary) -- Children's plays